Uporaba lesno-plastičnih kompozitov v tehnologiji 4D tiska - Krapež Tomec, Daša (Les (Ljubljana), 2021)
Three-dimensional (3D) printing with wood-plastic composites is already well known, and the use of wood in four-dimensional (4D) printing is being increasingly explored. 4D printing is an evolving area of additive technologies where, with the appropriate design of 3D printing and use of appropriate materials, we can create products that change shape and form dynamic structures when triggered externally. In 4D printing, the hygroscopicity of wood – usually considered a disadvantage – can be used as a positive property to design products that change their shape according to climatic conditions, especially humidity. In this research, we used the FDM (fused deposition modelling) technology of 3D printing PLA (polylactic acid) and wood-plastic composites (wood-PLA) to produce specimens with different material proportions, whose response to changing climatic conditions we monitored. To monitor the change in shape, or curvature, we fabricated composite test specimens using the bimetal principle (actuators), in which we used PLA for the passive layer and wood-PLA for the active layer in different thickness ratios and exposed them to laboratory and external conditions.The results showed that the wood content of the wood-plastic composites leads to dimensional changes in a changing climate, resulting in changes in the shape of the designed actuators. The change in shape depends on the thickness ratio of the layers in the two-layer actuator, the sorption of water vapor, and the wood content in the wood-plastic composite used
Keywords: 3D printing; 3D tisk; 4D printing; 4D tisk; les; lesno-plastični kompoziti; materiali z oblikovnim spominom; shape memory materials; wood; wood-plastic composites